Identification of Tapeworm Species in Genetically Characterised Grey Wolves Recolonising Central Europe - Juránková, Jana; Hulva, Pavel; Bolfíková, Barbora Černá; Hrazdilová, Kristýna; Frgelecová, Lucia; Daněk, Ondřej; Modrý, David (Acta parasitologica, 2021)
PURPOSE: Restored role of the grey wolf in ecological networks of newly recolonized areas can be studied via surveys of parasite communities of this predator. As helminths circulating in multi-host systems, the tapeworms directly reflect wolves' diet, while some species are also important from the One Health perspective. The Czech experienced centuries of wolves' absence, however, now it is situated on the crossroad of recolonising wolves' populations, which is opening questions of their role in ecological networks in this area and thus in sylvatic cycles of heteroxenous parasites. METHODS: Five wolf carcasses from this area were obtained and genetic affinity to a particular population was inspected. Tapeworms isolated from wolves' intestines during necropsies were molecularly identified based on sequences of COI marker. RESULTS: Three wolf haplotypes (w1, w2, w14) correspond with the dominance of haplogroup 1 (w1, w2) within Central European lowland population and haplogroup 2 (w14) within the Carpathian population. Two Taenia spp. were revealed: T. krabbei in Central European population wolves and T. hydatigena in an individual from Carpathian population. CONCLUSIONS: The results serve as a base for future monitoring and studies of the recolonising wolf population and its impact on ecosystems in the studied area to contribute to the hypothesis about differentiation of parasite communities in particular wolf population and higher parasite diversity and richness in established populations in comparison to newly settled ones.
Keywords: Animals; ekosystém; Ecosystem; Europe; Taenia; zvířata; Evropa; Grey wolf; vlci; Haplotypes; Tapeworms; Helminths; cizopasní červi; Wolves; Recolonising